2014
DOI: 10.1111/oik.01433
|View full text |Cite
|
Sign up to set email alerts
|

Priority effects vary with species identity and origin in an experiment varying the timing of seed arrival

Abstract: Exotic species are sometimes phenologically distinct from native species in the invaded community, allowing them to be active when there may be reduced competition for resources. In southern California, annual species are particularly problematic invaders, and prior work has shown that these species germinate earlier in the growing season, giving them a competitive advantage over later-germinating native species. Th is result begs the question, if being active earlier is advantageous, why have not native speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 52 publications
1
46
4
Order By: Relevance
“…dependent on site), are sometimes asymmetrical (i.e. benefit some guilds more than others; see also Blaisdell ; Cleland et al ; Vannette & Fukami ; Werner et al in press), and are of variable persistence.…”
Section: Discussionmentioning
confidence: 99%
“…dependent on site), are sometimes asymmetrical (i.e. benefit some guilds more than others; see also Blaisdell ; Cleland et al ; Vannette & Fukami ; Werner et al in press), and are of variable persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Though there is evidence that exotic species may benefit from early arrival to a greater extent than do natives (Dickson, Hopwood & Wilsey ), some studies have found no difference in the strength of priority benefits incurred by native and exotic plant species (Cleland, Esch & McKinney ). Such differences in results among studies likely stem from important differences among species and study systems, such as potentially different effects of priority on annual and perennial‐dominated systems (the Dickson, Hopwood & Wilsey () study took place in a perennial‐dominated system, while the Cleland, Esch & McKinney () study was in an annual‐dominated grassland in which only two of the eight study species were perennials). Our study provides a potential avenue by which priority effects may promote the success of exotic species, even in the absence of a strong benefit associated with early arrival.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of arrival also has the potential to influence our results. In this study, our early arrivers were added 2.5 weeks before late‐arriving species, which is well within the typical range of 1–3 weeks often used in studies of priority (Dickson, Hopwood & Wilsey ; Kardol, Souza & Classen ; Cleland, Esch & McKinney ). However, we might imagine that increasing the time between the addition of early‐ and late‐arriving species may serve to strengthen priority effects, though 2.5 weeks seems to be enough to elicit effects (Kardol, Souza & Classen ).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, a variety of relationships of the competition–phenology function fijfalse(normalΔ0.166667empij,tfalse) are possible, but biological systems generally fall in two broad categories (Wilbur & Alford ; Cleland et al ; Clay et al ): (1) Early arriver advantage, where negative effects of interspecific competition on a given species declines the earlier it arrives before others, and (2) late arriver advantage, where negative effects of interspecific competition on a species decrease when it arrives later than its competitors. The effect of shifts in phenologies depends on whether interacting species fall in opposite or the same arrival advantage category.…”
Section: Introductionmentioning
confidence: 99%